Direct normal irradiance predictions using broadband models for Indian stations - Laxmi Narain Rohilla; Dinesh Kumar Singh (Energy Reports, 2020)
In this paper three parametric models CPCR2, MLWT2 and REST have been used to compute direct normal irradiance (DNI) for five Indian stations, namely New Delhi, Pune, Jaipur, Kolkata and Mumbai. Computed values of DNI have been compared with measured values in terms of percentage root mean square error (RMSE) and percentage mean bias error (MBE). It is observed that the average percentage RMSE for the year is the minimum for MLWT2 model for Jaipur followed by New Delhi and Pune and the values are 1.67%, 2.33% and 2.49%, respectively. But for coastal stations Kolkata and Mumbai the corresponding minimum values occur for CPCR2 model and REST model respectively, and the values are 2.62% and 2.76%, respectively. It shows that MLWT2 model performs better for most of the Indian stations except the coastal stations.
Keywords: 330; Direct normal irradiance; Mean bias error; Root mean square error